Metalloproteases: On the Watch in the Hematopoietic Niche. Issue 11 (November 2019) - Saw, Sanjay; Weiss, Ashley; Khokha, Rama; Waterhouse, Paul D.
Abstract : Hematopoietic stem cells (HSCs) self-renew or differentiate into blood cell lineages following extrinsic cues propagated in specialized niches. Support cells and soluble factors in the niche respond to stress and enable progenitor activity. Metalloproteases (MMPs, ADAMs, ADAMTSs) and their inhibitors (TIMPs) control certain physical and biochemical features of the niche by altering protease-dependent bioavailability of local niche factors (e.g., CXCL12, SCF, TGFβ, VEGF), matrix turnover, and cellular interactions. With over 40 examples of diverse metalloprotease substrates known to trigger fate-changing decisions, the spatially confined activity of this multi-member protease family is ideally positioned to constitute a higher order control over hematopoiesis. Comprehension of regulated proteolysis in the bone marrow may fuel innovative strategies to harness HSC fate and function. Highlights: Metalloproteases and their inhibitors can impact the bioavailability of important local signals that instruct mammalian hematopoietic stem cell (HSC) fate and function in the hematopoietic niche. The metalloprotease network regulates the biomechanical and biochemical characteristics of the niche through the processing of the extracellular matrix, integrins, growth factors, and cell surface receptors. TIMPs can exert a multilayered regulation on HSCs via both protease-dependent and protease-independent actions on stromal and other cells. Despite growing evidence, metalloprotease/tissue inhibitors of metalloproteases (TIMP) proteins are currently underappreciated as important modulators of hematopoiesis.